Mobile agents modelling using UML. (2015) - Hanandeh, Feras Ahmad; Alsmadi, Izzat; Al-Shannag, Majdi Yousef; Al-Daoud, Essam
In software and system design, there are many views that can be demonstrated through visual diagram. State diagrams are widely used to express systems, entities or objects experiences different states according to different events or transitions. Typical state diagrams do not take the complexity of many currently existing systems. The singular view of definite possible states that a traditional state diagram allows is inapplicable for some hybrid complex systems such as mobile agents, graphical user interfaces, etc. In this paper, we take a look at the presented approach for modelling agent mobility with UML sequence diagrams and present a simplified form of UML state diagrams for modelling agent mobility. We proposed enhancements on the traditional state diagram to take into consideration modelling such hybrid complex systems as extension for the traditional state diagram. The concepts from the composite pattern are used in which there is a need for conformity in dealing with composite and component elements.